Transforming Pricing Strategies Globally Through Activity Based Costing - Miftakhul Jannah; Nurasik Nurasik (Indonesian Journal of Law and Economics Review, 2024)
This study evaluates the costing methods of Mami Pia & Cookies, using interviews, observations, and documentation to analyze their production costs. Results show that the company’s current full costing method aligns with accounting theories but is not fully integrated into their pricing strategy, especially for factory overhead. The study recommends adopting Activity Based Costing (ABC) to improve the accuracy of production cost calculations and pricing decisions, leading to more effective financial management and policy-making. Highlights: 1. Theoretical alignment of costing methods.2. Incomplete integration with pricing strategies.3. Recommendation: Adopt Activity Based Costing for accuracy. Keywords: Costing Methods, Mami Pia & Cookies, Activity Based Costing, Production Costs, Pricing Strategy